2011
DOI: 10.1021/pr200203v
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Pattern Recognition Can Distinguish Neuroinflammation and Peripheral Inflammation

Abstract: Multiple Sclerosis (MScl) is a neurodegenerative disease of the CNS, associated with chronic neuroinflammation. Cerebrospinal fluid (CSF), being in closest interaction with CNS, was used to profile neuroinflammation to discover disease-specific markers. We used the commonly accepted animal model for the neuroinflammatory aspect of MScl: the experimental autoimmune/allergic encephalomyelitis (EAE). A combination of advanced (1)H NMR spectroscopy and pattern recognition methods was used to establish the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…One of these metabolites-arginine was also identified by the targeted NMR method. Smolinska et al (2011) found that arginine, creatine and lysine changed in the CSF of EAE. Arginine involved pathways may be played in the onset of MS.…”
Section: Application Of Metabolomics In Multiple Sclerosismentioning
confidence: 96%
“…One of these metabolites-arginine was also identified by the targeted NMR method. Smolinska et al (2011) found that arginine, creatine and lysine changed in the CSF of EAE. Arginine involved pathways may be played in the onset of MS.…”
Section: Application Of Metabolomics In Multiple Sclerosismentioning
confidence: 96%
“…The experimental arrangement was as previously described by Smolinska et al and/or Hendricks [10, 11]. Here, we briefly summarize the main points.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling, sample preparation, and acquisition of CSF NMR spectral data were as described elsewhere [11]. Blood was sampled intravenously by use of a heparin-treated syringe.…”
Section: Methodsmentioning
confidence: 99%
“…10 mL). 22 The metabolic profiles derived from the two models of either peripheral inflammation (induced by complete Freund adjuvant (CFA) emulsion) or neurological inflammation were compared using Partial Least Squares Discriminant Analysis (PLS-DA) and ANOVA Principal Component Analysis (ANOVA-PCA). Neurological inflammation was manifest in the experimental autoimmune/allergic encephalomyelitis (EAE) model, induced by CFA and myelin basic protein (MBP), which has become an important tool in the understanding of human disease given the resemblance in clinical expression and pathology to that of multiple sclerosis, although the neurodegeneration and demyelination processes are not mimicked in this model.…”
Section: Immunologymentioning
confidence: 99%